Experimental study on the effect of low melting point metal additives on hydrogen production in the aluminum–water reaction. (August 2015) - Yang, Weijuan; Zhang, Tianyou; Zhou, Junhu; Shi, Wei; Liu, Jianzhong; Cen, Kefa
Abstract: Aluminum (Al) is a promising hydrogen carrier. Continuous reaction of pure Al and water (H2 O) cannot proceed smoothly because Al particles are covered with a protective oxide layer. Thus, 20% Mg, Li, Zn, Bi, and Sn content were added as additives to Al–H2 O reaction at high temperature. Thermogravimetric experiments were conducted to determine the reactivity of pure Al and five other samples with additives in a vapor atmosphere. Experiments indicated that Mg and Li drove the Al–H2 O reaction, but Zn, Bi, and Sn had little effect. Thus, Mg and Li were selected as activators in the hydrogen generation of the Al–H2 O reaction conducted on a specially designed experimental facility. Hydrogen was monitored in the reaction of Al-based composites with H2 O vapor in real time. Among them, Al–20%Li achieved the fastest hydrogen generation rate (309.74 ml s −1 g −1 ) and the largest hydrogen amount (1038.9 ml g −1 ). XRD (X-ray diffraction), SEM (scanning electron microscopy), and TEM (transmission electron microscopy) were used for product analyses to identify the influence of adding Mg and Li. This method of Al energy utilization may be used in underwater propulsion systems. Highlights: In this paper, we discussed a way of hydrogen production by the reaction of molten aluminum with water. 20% Mg, Li, Zn, Bi, and Sn content were added as additives to Al–H2 O reaction at high temperature. Al–20%Li achieved the fastest hydrogen generation rate and the largest hydrogen amount.